2020
DOI: 10.31410/balkans.jetss.2020.3.2.148-162
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Agile Software Architect in the Age of Digital Disruption and Transformation

Abstract: The consequence of the increasing development and use of digital technologies, in every segment of society, is the emergence of digital disruption - a powerful external pressure that is changing the way business is done in all industries. Businesses are responding to digital disruption by digital transformation, which involves organizational change, redefining and aligning digital and business strategies, new business models, increased agility of software development and delivery processes, migration and/or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…According to a 2020 Agile report, larger organizations are now using agile for quicker, simpler, and wiser app development. The agile poll in 2020 showed that 94% of tech companies are using agile strategies, and this agile methodology usage ratio is expanding globally too [7].…”
Section: The Agile Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a 2020 Agile report, larger organizations are now using agile for quicker, simpler, and wiser app development. The agile poll in 2020 showed that 94% of tech companies are using agile strategies, and this agile methodology usage ratio is expanding globally too [7].…”
Section: The Agile Methodologiesmentioning
confidence: 99%
“…The agile software development system is the result of this demand but still, further improvements are required. Agile architecture makes it simple to design software and use it in various settings [7]. Early software creation is aided by the agile approaches which are done in stages, with each release providing more working code and less documentation.…”
Section: Introductionmentioning
confidence: 99%